2012
DOI: 10.5194/esd-3-139-2012
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between metrics to compare greenhouse gases – the case of IGTP, GWP and SGTP

Abstract: Abstract. Metrics for comparing greenhouse gases are analyzed, with a particular focus on the integrated temperature change potential (IGTP) following a call from IPCC to investigate this metric. It is shown that the global warming potential (GWP) and IGTP are asymptotically equal when the time horizon approaches infinity when standard assumptions about a constant background atmosphere are used. The difference between IGTP and GWP is estimated for different greenhouse gases using an upwelling diffusion energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…(1), the impact is temperature, and the discount function is no discounting for t < H and full discounting for t > H . The iAGTP has been discussed indirectly by some authors (O'Neill, 2000;Gillett and Matthews, 2010), but in more detail in Peters et al (2011a); Azar and Johansson (2012). Preliminary work on the GWP was also based on integrated temperature change (Wuebbles, 1989;Derwent et al, 1990), but the link to temperature did not make it into the First Assessment Report (IPCC, 1990).…”
Section: Integrated Absolute Global Temperature Change Potential (Iagtp)mentioning
confidence: 99%
See 3 more Smart Citations
“…(1), the impact is temperature, and the discount function is no discounting for t < H and full discounting for t > H . The iAGTP has been discussed indirectly by some authors (O'Neill, 2000;Gillett and Matthews, 2010), but in more detail in Peters et al (2011a); Azar and Johansson (2012). Preliminary work on the GWP was also based on integrated temperature change (Wuebbles, 1989;Derwent et al, 1990), but the link to temperature did not make it into the First Assessment Report (IPCC, 1990).…”
Section: Integrated Absolute Global Temperature Change Potential (Iagtp)mentioning
confidence: 99%
“…Preliminary work on the GWP was also based on integrated temperature change (Wuebbles, 1989;Derwent et al, 1990), but the link to temperature did not make it into the First Assessment Report (IPCC, 1990). Peters et al (2011a); Azar and Johansson (2012) investigated whether the GWP was similar to the iGTP and found close agreement for a wide range of time horizons, but not for very SLCFs like BC. The similarity is since AGWP represents the total energy added to the system and iAGTP/λ the energy lost from the system.…”
Section: Integrated Absolute Global Temperature Change Potential (Iagtp)mentioning
confidence: 99%
See 2 more Smart Citations
“…The GWP compares the radiative forcing (RF) integrated from the time of emission until a specified time, the so-called time horizon (Shine et al, 1990), while the GTP compares the globalmean temperature change at a certain time after the emission (Shine et al, 2005). More recently, an integrated version of GTP was presented (iGTP), and this compares the temperature change integrated from the time of emission until a time horizon (Gillett and Matthews, 2010;Peters et al, 2011;Azar and Johansson, 2012). It is found that iGTP and GWP are 268 D. J. L. Olivié and G. P. Peters: Variation in emission metrics similar, with one quantifying the energy added to the system (GWP), and the other quantifying the energy lost (iGTP) (Peters et al, 2011;Azar and Johansson, 2012).…”
Section: Introductionmentioning
confidence: 99%